Differences in 30-15 IFT test performance across playing positions and categories among adult professional soccer players - Felipe Hermosilla-Palma; Rodrigo Villaseca-Vicuña; Pablo Merino-Muñoz; Nicolás Gómez-Álvarez; Jorge Pérez-Contreras; Miguel Salas-Ávila; Hugo Cerda-Kohler; Moacyr Portes-Junior; Esteban Aedo-Muñoz (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Objective: This study aims to assess the performance of professional soccer teams from different divisions and playing positions using the 30-15 intermittent fitness test (30-15 IFT). Methods: The sample comprised 84 male soccer players from first division teams A (1A) (n=21; mean age 23.5±5.2 years), first division B (1B) (n=42; mean age 23.0±5.0), and second professional division (2nd) (n=21; mean age 22.9±4.7 years). Performance was evaluated based on the final speed achieved in the 30-15 IFT (VIFT). Results: Significant differences were observed between 1A and both 1B and 2nd in VIFT (p=0.002, n2p=0.115). Additionally, differences were found between defenders and full-backs in VIFT (p=0.002, n2p=0.197). Conclusion: Performance in the 30-15 IFT varies across divisions, with 1A achieving the highest values. Moreover, full-backs demonstrated superior performance compared to defenders. These findings provide valuable insights for coaches, physical trainers, and sports scientists for optimizing training programs.